Landasan Psikologis Pendidikan Kristen Dan Relevansinya Dalam Pendidikan Kristen Masa Kini - Siringoringo, Lumayan (Sekolah Tinggi Teologi Sriwijaya, 2024)
This study examines the psychological foundation of Christianity and its relevance in contemporary Christian education. The development of a Christian institution cannot be separated from the concept of education in the institution. Education is an important reference in seeing, directing and bringing about a very significant and maximum change. In the midst of the rise of education today, Christian education is a type of education that should be taken into account, because it has contributed to building the morals, character and faith of many people. Therefore, Christian education needs to be continuously developed in such a way that it increasingly produces maximum positive impacts. By using a descriptive qualitative method, through a literature study approach, the research can describe the importance of psychological foundations as one of the elements that are very important to consider and apply in the process of Christian education. There are many people who have not implemented Christian education seriously and appropriately in contemporary Christian education. This can be seen from the morals, character and faith of some of the students who are not getting better, tend to stagnate and even decline. Researchers feel the need to link the progress of Christian education with building a strong psychological foundation so that it can be used as a reference in building an ideal and maximum Christian education. It is hoped that through this research, Christian educators can be equipped with the matter of bringing educational psychology into Christian education intelligently and politely, so that it effectively and efficiently brings about a very significant and maximum change for a Christian educational institution. The principles in this presentation will formulate several psychological foundations that are the foundations in Christian education.